Ghoulfriends 'til the end - Daneshvari, Gitty (Daneshvari, Gitty Monster High, 2014)
It is bad times at Monster High because a secret organization of older monsters is determined to preserve their hierarchy, and it is up to the ghoulfriends...Rochelle, Rebecca, and Venus...to stop ASOME, protect their school, and rescue their friends